Advances in human amniotic placenta membrane-derived mesenchymal stromal cells (hAMSCs) for regenerative medicine: enhancing therapeutic potential with biomaterials and scaffolds - de Laorden, Elvira H.; Rodilla, Beatriz L.; Arroyo-Hernández, María; Iglesias, Maite (Frontiers in Bioengineering and Biotechnology, 2025)
Mesenchymal stromal cells (MSCs) derived from the human placenta amniotic membrane (hAMSCs) have emerged as a promising option in regenerative therapies due to their multipotent differentiation and tissue regeneration capacity, low immunogenicity, and potent immunomodulatory properties. Compared to MSCs from other sources, such as bone marrow or adipose tissue, hAMSCs offer significant advantages, including higher proliferation, lower risk of immune rejection, and greater availability, as their collection is non-invasive and free of ethical concerns. These characteristics make them ideal candidates for regenerative medicine applications and the treatment of degenerative diseases. In this work, we review, from a preclinical perspective, the properties and therapeutic characteristics of hAMSCs derived from the human placenta, and the enhancement in their therapeutic properties when applied in combination with biomaterials such as natural and synthetic polymers or scaffolds, for the treatment of different disorders. The combination of hAMSCs with biomaterials and scaffolds provides a more efficient approach to tissue engineering, enhancing cell viability, proliferation, and integration into damaged tissues. Furthermore, we discuss the properties of scaffolds used to enhance the regenerative capacity of these cells, focusing on their biocompatibility, biodegradability, and ability to mimic the native extracellular matrix. This combined approach has the potential to revolutionize regenerative medicine, providing more effective and personalized therapies for a wide range of chronic and debilitating diseases.